2012
DOI: 10.12681/mms.307
|View full text |Cite
|
Sign up to set email alerts
|

New records of recently described chemosymbiotic bivalves for mud volcanoes within the European waters (Gulf of Cádiz)

Abstract: Chemosymbiotic bivalves are important members of cold seep communities and information on their distribution in the European waters is still quite scarce. This study reports the presence of living populations and shell remains of some recently described bivalves such as Lucinoma asapheus, Solemya elarraichensis and Acharax gadirae as well as Bathymodiolus sp. in the mud volcanoes of the Spanish Atlantic waters. Living populations of these species were thus far only found in Anastasya, Aveiro and Almazán mud vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…The Gazul mud volcano is located in the continental slope of the Gulf of Cadiz (Palomino et al, 2015). Gazul is sculpted by the MOW, which has carved two downstream depressions at both sides of the structure, whereas its rear sector has a peculiar saddle shape as result of the low velocities that enable sedimentation (Rueda et al, 2012;Palomino et al, 2016). The Ormonde seamount forms part of the Gorringe Bank at around 125-150 miles west-southwest of Cape St. Vincent.…”
Section: Area Of Studymentioning
confidence: 99%
“…The Gazul mud volcano is located in the continental slope of the Gulf of Cadiz (Palomino et al, 2015). Gazul is sculpted by the MOW, which has carved two downstream depressions at both sides of the structure, whereas its rear sector has a peculiar saddle shape as result of the low velocities that enable sedimentation (Rueda et al, 2012;Palomino et al, 2016). The Ormonde seamount forms part of the Gorringe Bank at around 125-150 miles west-southwest of Cape St. Vincent.…”
Section: Area Of Studymentioning
confidence: 99%
“…The absence of chemosymbiotic species in the samples is mainly due to the sampling method used, which mostly targets large epifaunal and demersal species, and to the fact that samples were taken in adjacent bottoms of mud volcanoes without fluid venting. Nevertheless, a recent study on infauna of mud volcanoes from El Laberinto (Anastasya, Pipoca and Tarsis) using different sampling methods (box-corer, benthic dredge, beam trawl) to the one used for this study (otter trawl) have highlighted the presence of chemosymbiotic bivalves, frenulate polychaetes and interesting habitats that deserve conservation (cold water corals, sponge and gorgonian aggregations) in these mud volcanoes (González-García 2011;Rueda et al 2012a;Rueda et al 2012b). Previous studies have also found chemosymbiotic-based communities in mud volcanoes on the Moroccan margin (Cunha et al 2002Rodrigues et al 2008;Vanreusel et al 2009;Oliver et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts the strong differences observed in the benthic communities and habitats of the summits and sides of mud volcanoes of El Laberinto using different sampling techniques (González-García 2011). These include chemosynthesis-based communities (Siboglinum sp., Lucinoma asapheus, Solemya elarraichensis) in Anastasya, sea-pen and burrowing megafauna communities (Funiculina quadrangularis, Kophobelemnon stelliferum, Pennatula aculeata, Isidella elongata) in Tarsis and sponge (Asconema, Petrosia, Haliclona, among others) and crinoid (mostly Leptometra phalangium) aggregations in Pipoca (González-García 2011; Rueda et al 2012b). Downloaded by [University of Sussex Library] at 07:03 03 February 2015…”
Section: Spatial Distribution Of Faunistic Assemblages Around Mud Volmentioning
confidence: 99%
See 2 more Smart Citations